Pengaruh Akuntabilitas terhadap Pengelolaan Keuangan Pemerintah Daerah: Tinjauan Literatur Sistematis dan Meta Analisis Sederhana - Rodhiyah Rodhiyah; Pramandyah Fitah Kusuma (Jurnal Mutiara Ilmu Akuntansi, 2025)
This study aims to synthesize empirical findings regarding the influence of accountability on local government financial management through a Systematic Literature Review (SLR) and a simple meta-analysis. A total of 10 primary studies (2020-2025) from various databases were analyzed. The results of the qualitative synthesis indicate a shift in research focus from compliance accountability to performance-based and digital accountability. Quantitatively, accountability was found to have a positive and significant influence on the quality of local financial management, mediated by variables such as transparency and internal control systems. The novelty of this study lies in the mapping of accountability and financial management indicators, as well as the identification of research trends leading to technology integration. These findings have important implications for the formulation of more effective and accountable local financial governance policies and results-oriented, which can ultimately improve the quality of public services and the sustainability of regional development. This is expected to improve the quality of public services and support the sustainability of regional development that is better, more transparent, and responsive to community needs.